Genome-Wide Survey of Donor Chromosomal Genes Involved in Trans-Kingdom Conjugation via the RP4-T4SS Machinery - Kazuki Moriguchi; Kazuyuki Nakamura; Yudai Takahashi; Kyoko Higo-Moriguchi; Kazuya Kiyokawa; Katsunori Suzuki (Microorganisms)
Trans-kingdom conjugation (TKC)/inter-domain conjugation is a horizontal gene transfer phenomenon that transfers DNA from eubacteria to eukaryotes and archaebacteria via a type IV secretion system encoded in IncP1-type broad-host-range plasmids. Although TKC is considered a potential gene introduction tool, donor chromosomal genes that influence TKC efficiency have rarely been analyzed, hindering targeted donor breeding. To identify potential TKC-related genes on a donor chromosome, a genome-wide screening of TKC-deficient mutants was performed using a comprehensive collection of Escherichia coli gene knockout mutants (Keio collection) as donors and a Saccharomyces cerevisiae strain as a recipient. Out of 3884 mutants, two mutants (∆aceE, ∆priA) showed a severe decrease in TKC efficiency by more than two orders of magnitude but not in bacterial conjugation. The effect on TKC efficiency by the two mutants was partly recovered by a preculture with a fresh culture medium before the TKC reaction, regardless of the presence of antibiotics. These results suggest that no single chromosomal target gene is solely responsible for universally blocking IncP1-type conjugation by impeding its function. The results also suggest the existence of an unidentified recognition or transfer mechanism distinct from bacterial conjugation, highlighting the novel roles of aceE and priA.